9. IMPLIKASI KEBIJAKAN ONE CHINA POLICY TERHADAP KEAMANAN TENAGA KERJA INDONESIA DI TAIWAN PERIODE TAHUN 2010-2014 - Leprilian, Yang; Windiani, Reni; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Taiwan holds a significance position for Indonesian economy, one of which can be seenfrom the large number of Indonesian Migrant Workers who work in the country. On theother hand, due to the One China Policy, Indonesia does not have diplomatic relations withTaiwan because Indonesia prefers to recognize the sovereignty of the People's Republic ofChina. Related to these facts, this research aims to determine and analyze the implicationsof the One China Policy toward the protection of Indonesian Migrant Workers in Taiwanbetween 2010 until 2014. Research frameworks used in this analysis are the concept ofhuman security, multi-track diplomacy and rational choice. The method of this research isqualitative with explanative type of research. From this research, it is known that theabsence of diplomatic relations between Indonesia and Taiwan, which are the consequenceof the One China Policy, has weakened the human security protection of the IndonesianMigrant Worker in Taiwan provided by the Government of Indonesia. In addition,inadequate protection of Indonesian Migrant Workers in Taiwan is also caused byspineless bargaining power possessed by Indonesia compared to Taiwan, especially inrespect to imbalance economic relationship between the two.